Efektivitas Pemanfaatan Rumpon Sebagai Alat Bantu Penangkapan Ikan pada Nelayan Lokal di Kelurahan Hamadi Kota Jayapura - Kalvin Paiki; Efray Wanimbo (Cenderawasih University, 2022)
Rumpon (Fishing Aggregating Devices/FADs) are fishing aids to lure fish to gather in an area. The use of FADs by Hamadi fishermen in Jayapura City is carried out by individual local fishermen with hand line fishing gear. This study aims to: 1) Know the composition of the catch (type and number of fish) on FADs, 2) Compare the effectiveness of FADs and fishing gear. This study used Qualitative and Quantitative Methods, data collection techniques consisted of a) Observation, b) Interview and c) Documentation study, analysis and to determine the composition of the catch, the effectiveness of FADs and the effectiveness of fishing gear. The results showed that the composition of the catch on FADs consisted of 19 species with 1,037 individuals per species, the highest species composition was found in Selar boops, which was 17.65% (183 individuals) and the lowest was found in Lutjanus Buccanella, namely 1.25% (13 individuals). . The highest effectiveness of assisted FADs was on Basic FADs, namely 60.46% (627 individuals) and the lowest on surface FADs, namely 39.54% (410 individuals), while the highest effectiveness of fishing gear used artificial bait, namely 53.81% (558 individuals) and the lowest was on natural baits namely 46.19% (479 tails). The conclusion is that the dominating fish species are Selar boops, bottom FADs are more effective than surface FADs, while the more effective fishing gear is using artificial baits.